2005
DOI: 10.1161/01.atv.0000161928.16334.dd
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cholesteryl Ester Transfer Protein Inhibition on High-Density Lipoprotein Subspecies, Apolipoprotein A-I Metabolism, and Fecal Sterol Excretion

Abstract: Objective-Pharmacological inhibition of the cholesteryl ester transfer protein (CETP) in humans increases high-density lipoprotein (HDL) cholesterol (HDL-C) levels; however, its effects on apolipoprotein A-I (apoA-I) containing HDL subspecies, apoA-I turnover, and markers of reverse cholesterol transport are unknown. The present study was designed to address these issues. Methods and Results-Nineteen subjects, 9 of whom were taking 20 mg of atorvastatin for hypercholesterolemia, received placebo for 4 weeks, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
150
2
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(163 citation statements)
references
References 53 publications
10
150
2
1
Order By: Relevance
“…A unique lipoprotein particle, LpAI:AII:E, with attenuated catabolism relative to LpAI, is present in patients with CETP deficiency and markedly increased plasma HDL cholesterol concentrations (127,128 ). Decreased catabolism of LpAI and LpAI:AII with increased HDL cholesterol concentrations has also been reported in patients treated with CETP inhibitors (52 ). Decreased plasma levels of LpAI and LpAI:AII are seen in hypertriglyeridemic patients because of increased catabolism of triglyceride-enriched LpAI and LpAI:AII (129,130 ).…”
Section: Apo Ai and Apo Ai:aii Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…A unique lipoprotein particle, LpAI:AII:E, with attenuated catabolism relative to LpAI, is present in patients with CETP deficiency and markedly increased plasma HDL cholesterol concentrations (127,128 ). Decreased catabolism of LpAI and LpAI:AII with increased HDL cholesterol concentrations has also been reported in patients treated with CETP inhibitors (52 ). Decreased plasma levels of LpAI and LpAI:AII are seen in hypertriglyeridemic patients because of increased catabolism of triglyceride-enriched LpAI and LpAI:AII (129,130 ).…”
Section: Apo Ai and Apo Ai:aii Particlesmentioning
confidence: 99%
“…Large ␣-1 particles increase with weight loss, niacin, certain statins (atorvastatin, rosuvastatin), and CETP inhibitors (52)(53)(54)(55)(56)(57). Increasing the concentrations of apo AI in ␣-1 HDL to Ͼ200 mg/L (0.52 mmol/L) with a simvastatin/niacin combination has been associated with lack of progression and in some individuals with regression of coronary atherosclerosis (51 ).…”
Section: -D Gel Electrophoresismentioning
confidence: 99%
“…Purifi ed HDL, but not LDL, signifi cantly enhanced inactivation of factor Va by activated protein C (APC) and protein S (69). HDL has also been shown to scavenge anionic phospholipids, pro-apoA-I or reconstituted HDL (rHDL; apoA-I purifi ed from human blood, reconstituted with phospholipids) was reported to result in an increase of sterol excretion (35,36) , but CETP inhibition (which blocks the exchange of cholesterol from HDL to LDL, resulting in a marked HDL-C increase as well as an LDL-C decrease) had no effect (37). Thus, human studies have only provided little evidence that HDL-C levels correlate with fecal cholesterol output.…”
Section: Other Potentially Atheroprotective Propertiesmentioning
confidence: 99%
“…A detailed description of the study design, depicted in Figure 1, has been reported previously. 8,9 All subjects received placebo for 4 weeks, followed by 120 mg torcetrapib once daily for an additional 4 weeks. Six subjects from the nonatorvastatin group also participated in a third phase, in which they received 120 mg torcetrapib twice daily for 4 weeks.…”
Section: Experimental Designmentioning
confidence: 99%
“…We reported previously that torcetrapib slowed the rate of clearance of apoA-I in plasma. 9 Here, we report the effects of torcetrapib on the metabolism of VLDL, intermediate-density lipoprotein (IDL), and LDL apoB100 in humans.…”
mentioning
confidence: 99%